The Effect of Blended Learning Based on The Problem-Based Learning Model Assisted by Puzzle Media on The Critical Thinking Skills of Fifth Grade Students on Ecosystem Themes - Hasna, Hanifah Rizki; Fajriyah, Khusnul; Saputra, Henry Januar (Universitas Pendidikan Ganesha, 2021)
The low competence of natural Science caused by using a learning model that is less than optimal makes it difficult for students to understand the learning material. This study aims to analyze the effect of blended learning based on a problem-based learning model assisted by puzzle media on the critical thinking skills of fifth-grade students on the ecosystem theme of SDN 03 Pegundan. This type of research is an experimental study using a pre-experimental design in the form of a one-group pretest-posttest design. The number of samples in this study was all students of class V SDN 03 Pegundan, totaling 26 students using saturated sampling type. Data collection in this study was obtained through interviews, tests, and documentation. The data analysis technique in this research is quantitative statistical data analysis techniques. This study obtained t-test results obtained t count > t table, 8.829> 1.706 and the results of hypothesis testing which stated that there was an effect of learning motivation, the regression test, the result was 62.1%. Based on the results of this analysis, it can be concluded that there is an effect of blended learning based on a problem-based learning model assisted by puzzle media on the critical thinking skills of fifth-grade students on the ecosystem theme of SDN 03 Pegundan.